FOOT REFLEXOLOGY FOR WOMEN AND FETAL WELLBEING IN LABOR : A REVIEW - Riska Ismawati Hakim; Nahdiyah Karimah; Putri M Saptyani; Sri Wahyuni M (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The secretion of catecholamine and epinephrine due to excessive fear and anxiety during labor will increase the intensity of pain and potentially prolonged labor. Reflexology massage leads to release endorphins and enkephalins which have an analgesic effect five times greater than morphine, creates a deep feeling of comfort and balance of mind so the stress symptoms are reduced, and improves the outcomes of labor. This study aims to analyze the effects of foot reflexology for women and fetal wellbeing in labor. Methodology: This systematic review used PRISMA-P (Preferred Reporting Items for Systemic Review and Meta-Analysis Protocols). The keywords used were reflexology or foot feflexology, pain relief, labor pain, primiparaous, effect or effectiveness. Articles were searched through databases PubMed, Google Scholar, and Science Direct. Inclusion were articles that discusssed about reflexology and its effects in labor, experimental research and written in English. The selected articles were excluded for irrelevant titles and abstracts, non-full text, research under 2009 and duplicate articles. From 78 articles, only 8 articles were included in this systematic review. Results: This study found that foot reflexology can reduce the intensity of labor pain. It was also decreased duration, anxiety, hemorrhage rate, systolic and diastolic blood pressure, pulse and increased uterine contractions, Apgar scores and maternal satisfaction with a highly statistical significant. Conclusion: Foot reflexology could decrease the intensity of labor pain, anxiety, duration, maternal complications and increase uterine contractions. In addition to improve labor outcomes and mother satisfaction. It is recommended as non pharmacological method which can be applied in maternity hospitals to improve women and fetal wellbeing during labor.